Hedonic price function for residential area focusing on the reasons for residential preferences in Japanese metropolitan areas - Mitsuru Sasaki; Kayoko Yamamoto (Journal of Risk and Financial Management, 2018)
This study aims to offer a new estimate of the hedonic price function of residential areas in Japanese metropolitan areas, focusing on the reasons for residential preferences. More specifically, it introduces two new explanatory variables-'regional vulnerability' and 'accessibility to destination stations'-and determines their usefulness. Based on the evaluation done in this study, the hedonic price function mentioned above showed 60% interpretability (as compared to 52% interpretability by hedonic price function using only conventional explanatory variables.) In addition, the significance level of both the explanatory variables was low, and the land price changed by 9% as the regional vulnerability changed by 1 grade. Furthermore, residents placed great emphasis on both variables. This made it evident that the introduction of the two explanatory variables that reflect the reasons for residential preferences specific to Japanese metropolitan areas was reasonable.
Keywords: 330; hedonic price functions; land price; residential area; residential preferences; regional vulnerability; accessibility to destination stations; multiple regression analysis; Geographic Information Systems (GIS)